Analisa Rencana Anggaran Biaya Untuk Efisiensi Studi Kasus Pembangunan Rumah Tinggal 2 Lantai - Rafi Ramadhan; Amri Gunasti (CV. Akira Java BUlu, 2026)
The Cost Estimate (RAB) is a crucial component in planning a two-story residential construction project, which is more intricate and complex than building a single-story house; therefore, an efficient cost estimate is required to minimize costs without compromising safety or the structural integrity of the building. This study aims to analyze cost components within the BEP that have the potential to cause cost overruns without compromising the quality of the building itself. The methods used are quantitative and descriptive analysis, reviewing BEP data from the perspectives of preparatory work, structure, architecture, and finishing. The analysis results indicate that expenditures can be made more efficient by re-evaluating the selection of more economical materials that still meet technical standards. Additionally, efficiency can be further enhanced by implementing good project management and eliminating non-essential expenditures. Thus, a comprehensive evaluation of the cost estimate can produce a more efficient and effective budget plan for the construction of a two-story house.